Spatial determinants of poverty in rural Kenya: A national and provincial analysis - Okwi, P.; Ndeng'e, G.; Kristjanson, Patricia M.; Arunga, M.; Notenbaert, An Maria Omer; Omolo, Abisalom; Henninger, N.; Benson, T.; Kariuki, P.; Owuor, J. (National Academy of Sciences, 2007)
This article investigates the link between poverty incidence and geographical conditions within rural locations in Kenya. Evidence from poverty maps for Kenya and other developing countries suggests that poverty and income distribution are not homogenous. We use spatial regression techniques to explore the effects of geographic factors on poverty. Slope, soil type, distance/travel time to public resources, elevation, type of land use, and demographic variables prove to be significant in explaining spatial patterns of poverty. However, differential influence of these and other factors at the location level shows that provinces in Kenya are highly heterogeneous; hence different spatial factors are important in explaining welfare levels in different areas within provinces, suggesting that targeted propoor policies are needed. Policy simulations are conducted to explore the impact of various interventions on location-level poverty levels. Investments in roads and improvements in soil fertility are shown to potentially reduce poverty rates, with differential impacts in different regions.